The Effect of Entrepreneurial Orientation on Performance Mediated by Innovation and Network Capability - Permatasari, Ayu Ervin Dea; Praswati, Aflit Nuryulia (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The development of the woodworking industry in Indonesia can be a highlight in the business world. However, 2020 is a year that gives a different color to the business world. The entry of the COVID-19 outbreaks into Indonesia in the first quarter of 2020 caused all industrial sectors including the manufacturing industry in Indonesia to experience a decline. The aim of this research is to analyze the influence of Entrepreneurial Orientation on Performance mediated by Innovation and Network Capability (Study at UD. Kondang Jaya Furniture and UD. Aryajati Furniture). This research method is quantitative. The population in this study were employees of UD Kondang Jaya Furniture and UD Aryajati Furniture. The number of samples in this research was 100 respondents. The sampling technique uses non-probability sampling with purposive sampling technique. The data source used in this research is primary data. The data analysis technique in this research was carried out using SMARTPLS 3.0 software. This research uses Structural Equation Model (SEM) analysis with Partial Least Square (PLS). Entrepreneurial Orientation has a positive and insignificant effect on Performance. Entrepreneurial orientation has a positive and significant effect on innovation. Entrepreneurial Orientation has a positive and significant effect on Networking Ability. Innovation has a positive and significant effect on performance. This means that the fourth hypothesis is accepted. Network Capability has a positive and significant effect on Performance. Innovation can mediate the influence of Entrepreneurial Orientation on Performance positively and significantly. Network Capability can mediate the influence of Entrepreneurial Orientation on Performance positively and significantly.